1991
DOI: 10.1002/jsfa.2740560102
|View full text |Cite
|
Sign up to set email alerts
|

Review on the significance of starch and protein to wheat kernel hardness

Abstract: A B S T R A C T Wheat starch contains large lenticular (A-type) and small spherical (B-type) granules, with some intermediate (underdeveloped

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 22 publications
9
43
1
2
Order By: Relevance
“…3), indicating that kernel texture is primarily controlled by one gene. Those findings concur with previous studies (Anjum and Walker 1991;Giroux and Moms 1998). As described below, the set of samples under study displayed a similar range in trait data compared with those found in US wheat breeding programs and other studies.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…3), indicating that kernel texture is primarily controlled by one gene. Those findings concur with previous studies (Anjum and Walker 1991;Giroux and Moms 1998). As described below, the set of samples under study displayed a similar range in trait data compared with those found in US wheat breeding programs and other studies.…”
Section: Resultssupporting
confidence: 94%
“…(1989) reported high phenotypic associations between FY and SE for soft wheat cultivars grown in many locations. The association between measures of kernel texture and FY suggests that the Ha gene, located on chromosome 5 D, which controls wheat texture either also influences FY or harder wheats simply mill more efficiently (Anjum and Walker 1991). Either way, it is apparent that soft wheat breeders have an opportunity to increase FY by making soft by hard wheat crosses.…”
Section: Resultsmentioning
confidence: 99%
“…The common wheat structure ( Figure 2C) is more similar to that of the vitreous emmer than to the floury emmer, as it exhibits an intimate contact between the starch granules and the cementing protein. This typical structure of hard wheat kernel has also been described by other authors (Anjum & Walker 1991;Rojas et al 2000;Jackowiak et al 2005). As regards the observation of the flours by SEM technique, spring vitreous emmer flour ( Figure 3A) and common wheat flour ( Figure 3C) showed a coat of protein covering the starch granules in some areas.…”
Section: Sds-page Of Gluten Proteinssupporting
confidence: 84%
“…The statistical analysis revealed that moisture, crude protein, crude fat and NFE contents of flour differed highly significantly (P<0.01) while crude fibre and total ash contents showed the significant (P<0.05) results. The results of the present study was found in agreement with the earlier finding of Ahmed (2001) who observed crude protein, crude fibre, ash, crude fat, moisture and NFE content in the range of 10.15-13.76%, 1.32-1.85%, 2.31-2.99, 1.96-2.52, 9.38- (Anjum and Walker, 1991). pH and titratable acidity: The mean values presented in Table 5 indicated that pH and TTA of sourdough breads varied from 4.70 to 5.17 and 3.47 to 4.60% among the treatments, respectively.…”
Section: Proximate Analysissupporting
confidence: 93%